Advance directives in the provision of care for incarcerated adults: a scoping review protocol. (June 2016) - Hand, Mikel W.; Mitchell, Sheryl; DeGregory, Cristy
Abstract : Scoping review question/objective: The objective of this review is to map the available evidence around advance directives in the care of incarcerated adults in terms of what has been undertaken, what outcomes have been reported, and what research gaps exist. The specific areas of investigation will include: Practices, policies or interventions used with incarcerated adults concerning advanced directives. Prisoners' experiences with advanced directives when receiving care. Barriers to establishing and implementing advanced directives. Healthcare providers' experiences with implementing advanced directives while providing care. The specific questions for this scoping review are: What types of research related to advanced directives in the provision of care for incarcerated adults have been conducted and reported? What research gaps exist in this area? Center conducting the review: The Indiana Centre for Evidence-Based Nursing Practice: a Collaborating Centre of the Joanna Briggs Institute